2012
DOI: 10.1002/ana.23738
|View full text |Cite
|
Sign up to set email alerts
|

25‐Hydroxyvitamin D and symptomatic ischemic stroke: An Original Study and Meta‐Analysis

Abstract: In this large population-based prospective study, we observed stepwise increasing risk of symptomatic ischemic stroke with decreasing plasma 25-hydroxyvitamin D concentrations. This finding was substantiated in a meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
133
3
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(156 citation statements)
references
References 39 publications
14
133
3
6
Order By: Relevance
“…A recent metaanalysis of prospective observational studies revealed an inverse relationship between levels of 25(OH)D 3 and risk of CVD, including coronary heart disease, stroke, and total CVD mortality (473). These increased risks for coronary heart disease and ischemic stroke or cerebrovascular disease for individuals with the lowest 25(OH)D 3 levels were also observed in other meta-analyses (60,61,82).…”
Section: Vitamin D: Pleiotropic Effectsmentioning
confidence: 78%
“…A recent metaanalysis of prospective observational studies revealed an inverse relationship between levels of 25(OH)D 3 and risk of CVD, including coronary heart disease, stroke, and total CVD mortality (473). These increased risks for coronary heart disease and ischemic stroke or cerebrovascular disease for individuals with the lowest 25(OH)D 3 levels were also observed in other meta-analyses (60,61,82).…”
Section: Vitamin D: Pleiotropic Effectsmentioning
confidence: 78%
“…Latitude, season, cultural norms, religious practices, low awareness, low knowledge/health literacy, indoor lifestyles, urban living, skin pigmentation, malnutrition, diet, co-morbidities like tuberculosis, and drugs may contribute to vitamin D deficiency especially in the in the developing world, moreover, blacks tend to have lower levels of 25(OH)D compared to whites [2,3]. It has been widely demonstrated that Vitamin D is also involved in different non-skeletal functions, including hypertension, diabetes, multiple sclerosis, Alzheimer's disease, Parkinson's disease, and Stroke [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A large body of evidence from epidemiological studies indicates that vitamin D deficiency is associated with an increased risk of stroke 12 , and Stepwise decrease in plasma 25(OH)D concentrations were associated with stepwise increasing risk of ischemic stroke 1 . To the best of our knowledge, no previous work has focused on the association between 25(OH)D and acute stroke in Bangladeshi population.…”
Section: Discussionmentioning
confidence: 99%